2 - Gender masked or self-inflicted pain: female circumcision, eradication and persistence in Central Kenya - Beth Maina Ahlberg,; Wangui Njau,; Karanja Kiiru,; lngela Krantz, (African Sociological Review, 2000)
Abstract